The French colonial policy in the religious field between Algeria and Morocco similarities and differences - boukidah, naam (Journal of Social Sciences and Humanities, 2021)
The French realized how much is strong the relationship between the centrality of religion and the social construction of their colonies in North Africa because of their religious and ethnic specificity, and it is totally different from their colonies in black Africa or Southeast Asia, therefore they tried to control it; we have noticed that the French policy in the religious field between Algeria and Morocco is different, therefore in this study we tried to highlight the similarities and differences in this policy and find out the reasons behind it. and we finally concluded the total difference in religious policy between the two colonies, this difference was the result of the conditions of time and That in each colony separately.